Методы расчета полей концентрации токсичных веществ и токсодоз при авариях на опасных химических объектах - Il’yushonok Александр; Leshenyuk Николай; Otchik Владимир; Popov В. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2013)
We discuss a number of methods for calculation of the pollutants concentration fields in the atmosphere. More sophisticated methods as compared to the technique «Toxi-2» for calculation of the parameters are analyzed, that can significantly affect the accuracy of the calculation. It is shown that taking into account the proposed improvements to the technique «Toxi-2» can be successfully used to solve various tasks in the field of ecology and emergency situations elimination.